Understanding the Link Between Collagen Composition and Extracellular Matrix Driven Changes in Breast Cancer Cell Metabolism - Nasreen, Amreen. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Irene Georgakoudi.; Committee: Madeleine Oudin, and Gail Sonenshein.; Keyword: Biomedical engineering.